Health education: an articulating axis of the Mexican educational curriculum - Zulema de la Caridad Matos Columbié; Susana Angelica Pastrana Corral; Guadalupe Quijada Fierros; Rosario Adalberto Mondaca Corral; Harold Joshua Gama Celaya (Revista Información Científica)
Introduction: health education seeks the well-being of people's health; For this reason, knowledge, skills and values are offered that strengthen this important area of life, which is why a psycho-pedagogical approach is needed.